PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV B SD NEGERI 41 DURI BARAT KECAMATAN MANDAU - Sani, Dian; Marhadi, Hendri; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:Low student learning outcomes can be seen from the beginning of learning outcomes data. Therefore, this model is applied to increase the yield of Quantum Teaching IV B class IPS SD 41 Duri Barat. Purposes of applying this model to improve student learning outcomes grade IV B 41 Duri West. This research is a classroom action research (CAR) conducted two cycles. To improve learning outcomes IPS grade IV B  41 Duri Barat, then applied the model Quantum Teaching. Subjects in this study were students of class IV B SD 41 Duri Barat, as many as 26 students, consisting of 16 male students and 10 female students. The percentage of teacher activity in cycle 1 meeting 75% increase in first at the meeting of 2 to 79%. And the second cycle of meeting 1 meeting 87.5% 2 95%. The percentage of student activity cycle I meeting 1, meeting 62.5% 2 65% while the second cycle 1 meeting increased to 82.5% Meeting 2 90%. While the average student learning outcomes preliminary data 59.42 students who graduated were 9 people (34.61%) did not complete the 17 subjects (65.39%). My daily test the thoroughness of the first cycle increased to 69.04 students who completed the 16 (61.53%) and did not complete the 10 (38.47%) experienced a 16.17% increase learning outcomes. Meanwhile, the second cycle of daily test II increased by an average value of 77.50 students who graduate as many as 23 people (88.46%) and unfinished 3 people (11.54%) increased by 30.42%. The study hypothesis was that if implemented the model of Quantum Teaching can improve learning outcomes IPS grade IV B SD 41  Duri Barat. KeyWords: Quantum Teaching, learning outcomes IPS